Corner Defect Detection Based On Inverse Trigonometric Function Using Image of Square Ceramic Tiles (International Journal of Engineering and Computer Science, 2014)
Today Ceramic Tile is mostly used in construction of floor at home, offices and shops and many other places. For user needs the ceramic tile industry demand increase, thus tile industry also increases the production, but the quality maintaining or quality control is also an important factor. This factor is directly related the production of ceramic tile. If quality is maintaining manually, it takes lots of time and some minor defect not finding by this process. In this paper we find corners defects of the ceramic tiles. We use image processing and Inverse Trigonometric Function. The angle of each corner square ceramic tile is equal to 90˚ means it is normal. Our proposed algorithm is classified in Upgraded Automatic Quality Maintaining Machine (UAQMM). By proposed algorithm we increase the efficiency rate and decrease the total computational time.